1977
DOI: 10.1002/ana.410020503
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic use of glucocorticoid hormones in the perinatal period: Potential neurological hazards

Abstract: The expanding perinatal use of glucocorticoids entails potentially hazardous effects of these hormones on nervous system development. Neonatal animal experimentation with pharmacological doses of glucocorticoids has revealed immediate effects on brain cell division, differentiation, myelination, and electrophysiological reactions. In addition, delayed (latent) effects include changes in control of circadian periodicity, altered biogenic amine levels, altered response to stress, and changes in ultimate behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(39 citation statements)
references
References 27 publications
3
34
0
2
Order By: Relevance
“…These results were consistent with previous animal experiments, which had shown that glucocorticoids administered during critical periods of brain development may impair myelinization, brain cell division, and longer-term behavioral effects. [11][12][13][14]16 As a result of these observations, neonatologists began to abandon PNSs for CLD when they learned of the longterm toxicities associated with PNS use for CLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with previous animal experiments, which had shown that glucocorticoids administered during critical periods of brain development may impair myelinization, brain cell division, and longer-term behavioral effects. [11][12][13][14]16 As a result of these observations, neonatologists began to abandon PNSs for CLD when they learned of the longterm toxicities associated with PNS use for CLD.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Metaanalyses of early (Ͻ96 hours of age) 7 and later use of PNSs to reduce CLD 8,9 demonstrated significant benefits with regard to earlier extubation and decreased risks of CLD at both 28 days and 36 weeks, death, or CLD at 28 days and 36 weeks, but there was a disturbing tendency toward an increase in neurodevelopmental impairment consistent with previous animal experiments, which had shown that glucocorticoids administered during critical periods of brain development may impair myelinization, brain cell division, and longer-term behavioral effects. [10][11][12][13][14][15][16] The American Academy of Pediatrics Committee on the Fetus and Newborn cautioned that PNS use outside of randomized trials should be reserved for "exceptional clinical circumstances." 17 The use of PNSs for the prevention or treatment of CLD remains common, especially for the extremely low birth weight infant (ELBW) whose birth weight is Ͻ1000 g, and information from the Vermont Oxford Network (VON), of which the California Perinatal Quality Care Collaborative (CPQCC) is a contributing member, indicates that for the year 2001, 38% of ELBW infants (22-65%) received PNSs.…”
Section: Authorsmentioning
confidence: 99%
“…Earlier studies with animals found a variety of alterations in neurobehavioral outcome following PNS exposure (Benesova & Pavlik, 1989;Meaney & Stewart, 1981;Weichsel, 1977). Studies on sheep found that greater exposure to early steroid decreased fetal growth (Jobe, Wadda, Berry, Ikegami, & Ervin 1998).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…They were used to aid in decreasing infant dependence on ventilators and on oxygen (Halliday & Ehrenkranz, 2001a, 2001b. At school-age follow-up, preterm infants whose chronic lung disease was treated with long-term steroid tapering doses were identified to have poor neurodevelopmental outcomes (Yeh et al, 2004).Earlier studies with animals found a variety of alterations in neurobehavioral outcome following PNS exposure (Benesova & Pavlik, 1989;Meaney & Stewart, 1981;Weichsel, 1977). Studies on sheep found that greater exposure to early steroid decreased fetal growth (Jobe, Wadda, Berry, Ikegami, & Ervin 1998).…”
mentioning
confidence: 99%
“…Accumulating evidence from clinical trials has also demonstrated an association between postnatal steroid therapy and adverse neuromotor and cognitive outcomes (4,5). Furthermore, experimental studies in neonatal animals have demonstrated adverse effects of potent glucocorticoids, such as dexamethasone, on brain growth, cell division, differentiation, myelination, apoptosis, and neurogenesis (6)(7)(8).…”
mentioning
confidence: 99%